Concrete pump working capacity determination in the composition of small-sized technological set equipment for the wet method gunite work - Emeljanova, Inga; Chayka, Denys; Bondar, Viktor; Virchenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2018)
The small-sized technological set equipment with a universal, non-porous hose concrete pump is shown, that is verified during the execution of wet method gunite work. Dependencies for determination of basic universal hose concrete pump work parameters are proposed. The stand surface concreted with wet-cracking method, by the using of the concrete mixture composition, which has been checked during the gunite work execution on the construction site. A check of the resulting rubber-concrete coating strength has been carried out. The stability of the offered technological package operating conditions is confirmed.